2000
DOI: 10.1074/jbc.275.18.13529
|View full text |Cite
|
Sign up to set email alerts
|

Role of Individual Monomers of a Dimeric Initiator Protein in the Initiation and Termination of Plasmid Rolling Circle Replication

Abstract: Plasmids of the pT181 family encode initiator proteins that act as dimers during plasmid rolling circle (RC) replication. These initiator proteins bind to the origin of replication through a sequence-specific interaction and generate a nick at the origin that acts as the primer for RC replication. Previous studies have demonstrated that the initiator proteins contain separate DNA binding and nicking-closing domains, both of which are required for plasmid replication. The tyrosine residue at position 191 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Therefore, we tested whether the heterologous helicases can promote replication of plasmid pT181 DNA in vitro. For these studies, cell extracts were prepared from the pcrA3 mutant of S. aureus as described earlier (4,5). The mutant PcrA3 helicase is inactive in plasmid pT181 replication but retains functions required for cell growth and viability (5,12,29).…”
mentioning
confidence: 99%
“…Therefore, we tested whether the heterologous helicases can promote replication of plasmid pT181 DNA in vitro. For these studies, cell extracts were prepared from the pcrA3 mutant of S. aureus as described earlier (4,5). The mutant PcrA3 helicase is inactive in plasmid pT181 replication but retains functions required for cell growth and viability (5,12,29).…”
mentioning
confidence: 99%
“…as described earlier (8). The MBP-RepS protein was purified by chromatography on an amylase affinity column, and the protein was eluted using the above buffer in the presence of 10 mM maltose (8). The purity of the protein was tested by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and staining with Coomassie brilliant blue.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in Luria-Bertani broth supplemented with 10 mM glucose at 37°C to the mid-exponential phase, and the MBP-RepS protein was overexpressed by induction with 1 mM isopropyl-␤-Dthiogalactopyranoside (IPTG) at 30°C for 2 h. The cells were lysed by several freeze-thaw cycles in a buffer containing 20 mM Tris-HCl (pH 8), 0.1 mM EDTA, 1 M NaCl, 10% glycerol, and Complete protease inhibitor cocktail tablets (Roche Molecular Biochemicals, Indianapolis, Ind.) as described earlier (8). The MBP-RepS protein was purified by chromatography on an amylase affinity column, and the protein was eluted using the above buffer in the presence of 10 mM maltose (8).…”
Section: Methodsmentioning
confidence: 99%
“…This assumption could be valid for plasmids of the pT181 family, as the sequence-specific DNA binding and DNA relaxation activities of RepC, the initiator of pT181, are mutationally separable and lie on distant protein regions (86). Taking advantage of this property, the identification of the role of individual monomers of pT181-RepC in RCR was addressed by generating heterodimers of the initiator containing a combination of wild-type, DNA binding, and nicking mutants (89). The results demonstrated that a single monomer of RepC is sufficient for origin-specific binding and nicking.…”
Section: The Replication Initiator Rep Proteinsmentioning
confidence: 99%
“…The results demonstrated that a single monomer of RepC is sufficient for origin-specific binding and nicking. In addition, the monomer involved in sequence-specific binding to the dso must also nick the DNA to initiate replication (89).…”
Section: The Replication Initiator Rep Proteinsmentioning
confidence: 99%